Hydrogeochemical and stable isotope data of groundwater of a multi-aquifer system: Northern Gafsa basin – Central Tunisia. (February 2016) - Mokadem, Naziha; Demdoum, Abedslem; Hamed, Younes; Bouri, Salem; Hadji, Rihab; Boyce, Adrian; Laouar, Rabah; Sâad, Abedaziz
Abstract: The hydrodynamic of the multi-aquifer system (the Continental Intercalaire " C.I " and the Complex Terminal " C.T ") of the North Gafsa basin is largely determined by tectonics (Tebessa – Gafsa fault). The composition of groundwater is controlled by complex reactions at gas-liquid-solid "mineralogical composition of associated rocks" interfaces, which depend on the natural surrounding and potential anthropogenic impact. The hydrochemical data (major ion geochemistry) indicate that these groundwaters are characterized by the dominance a Ca–Mg–HCO3 /SO4 and Na–Cl–NO3 water types. Geochemical pattern is mainly controlled by the dissolution of halite, gypsum and/or anhydrite as well as by the incongruent dissolution of carbonate minerals. The pH of these samples range from 6.54 to 8.89, supporting the conclusion that the H2 CO3 /HCO3 couple control pH buffering. Oxygen-18 (δ 18 O‰SMOW ) and deuterium (dD‰SMOW ) isotopic data show the exchange between the groundwater and the rock (water–rock interaction) and the evaporation effect. The isotopic content of the boreholes waters is of mixed Mediterranean - Atlantic origin and is opposite to the quantity of rainwater distribution, both in space and time in the study area. This is due to its geographical situation in the southern and south-western of the Mediterranean Sea and between the Atlas area and the Sahara Platform. The concentrations of the isotopic composition of the groundwater are significantly higher than the rainwater. This is indicative of the dissolution of salts and other processes modifying the rainwater geochemical composition during infiltration into the vadose zone. The hydraulic interconnection of these components of the system has led to the evolution of these interesting groundwater types. Highlights: Hydro and isotope geochemistry were used to identify the hydrodynamic functioning of the multi-aquifer system. And to identify the inter-aquifer mixing. And to investigate the water type of groundwater in the semi-arid southwestern Tunisia.